The OECD's "Action Plan" to raise taxes on multinational corporations - Hufbauer, Gary Clyde; Jung, Euijin; Moran, Tyler; Vieiro, Martin (Washington, DC, 2015)
"Hufbauer and colleagues critically evaluate the Organization for Economic Cooperation and Development’s ambitious multipart project titled Base Erosion and Profit Shifting (BEPS), which contains 15 "Actions" to prevent multinational corporations (MNCs) from escaping their "fair share" of the tax burden. Spurred by G-20 finance ministers, the OECD recommends changes in national legislation, revision of existing bilateral tax treaties, and a new multilateral agreement for participating countries. The proposition that MNCs need to pay more tax enjoys considerable political resonance as government budgets are strained, the world economy is struggling, income inequality is rising, and the news media have publicized instances of corporations legally lowering their global tax burdens by reporting income in low-tax jurisdictions and expenses in high-tax jurisdictions. Given that the US system taxes MNCs more heavily than other advanced countries and provides fewer tax incentives for research and development (R&D), implementation of the BEPS Actions would drive many MNCs to relocate their headquarters to tax-friendly countries and others to offshore significant amounts of R&D activity."